(3QSGdI aj GdWHjYjGJs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdebGdI GdKGfjI ef GdWHjYjGJ ai dhGMb GdWHjYI GYfi GdMQcI hGdSchf s
(3BNQgG (B:s
(3CeG Cf jchf jWdH Pdc GdLGfH HYjfg GhjWdH Ci MOjK jchf HYOg s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs